1999
DOI: 10.1161/01.atv.19.4.967
|View full text |Cite
|
Sign up to set email alerts
|

Increased Plasma 7β-Hydroxycholesterol Concentrations in a Population With a High Risk for Cardiovascular Disease

Abstract: Abstract-The mortality in coronary heart disease among 50-to 54-year-old men is 4 times higher in Lithuania than in Sweden. It was recently suggested that traditional risk factors could not explain this mortality difference. LDL of Lithuanian men showed, however, a lower resistance to oxidation than that of Swedish men. In addition, the plasma concentration of ␥-tocopherol, lycopene, and ␤-carotene were lower in Lithuanian men. In the present investigation, we determined plasma oxysterols in men from Lithuania… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
54
0
1

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 25 publications
8
54
0
1
Order By: Relevance
“…Of note, the oxysterol mixture employed (2 × 10 -5 M) is representative of oxysterol concentration present in vascular lesions (Leonarduzzi et al, 2007) while it is detectable in low concentration in oxLDL (i.e. within 10 -7 -10 -8 M range) (Ziedén et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the oxysterol mixture employed (2 × 10 -5 M) is representative of oxysterol concentration present in vascular lesions (Leonarduzzi et al, 2007) while it is detectable in low concentration in oxLDL (i.e. within 10 -7 -10 -8 M range) (Ziedén et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, a pathophysiologically relevant concentration of oxysterols has been consistently detected in the plasma of hypercholesterolemic subjects and in human atherosclerotic lesions (Brown & Jessup, 1999;Ziedén et al ., 1999;Schroepfer, 2000;Iuliano et al ., 2003;Leonarduzzi et al ., 2007). These compounds, of both dietary and metabolic origin, are known to exert a large variety of biochemical activities (Brown & Jessup, 1999;Leonarduzzi et al ., 2002), and their potential role in the pathogenesis of age-related diseases, proposed more than a decade ago, is now receiving more appropriate attention (Leonarduzzi et al ., 2005a,b;Vaya & Schipper, 2007).…”
Section: Introductionmentioning
confidence: 91%
“…[23][24][25][26][27][28][29] Moreover, the major products of cholesterol autoxidation are the most commonly detected oxysterols in foods (7K, 7␣OH, 7␤OH, ␣-EPOX, and ␤-EPOX). 29 Various oxysterols have been detected in extensive amounts in human tissues and fluids, including human plasma, atherogenic lipoproteins, and atherosclerotic plaque.…”
Section: Discussionmentioning
confidence: 99%
“…Lizard et al 25 and Deckert et al 27 observed that 7␤OH inhibited arterial relaxation and had the greatest ability to induce apoptosis in endothelial cells of all cholesterol oxides measured. Recently, Zieden et al 28 reported that elevated plasma 7␤OH concentration is an indication of an increased in vivo lipid peroxidation. For these reasons, we regarded 7␤OH as the most important cholesterol oxidation measure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation